2014
DOI: 10.1016/j.febslet.2014.10.038
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation dynamics of a maternally methylated DMR in the mouse Dlk1Dio3 domain

Abstract: The mouse delta‐like homolog 1 and type III iodothyronine deiodinase (Dlk1–Dio3) imprinted domain contains three known paternally methylated differentially methylated regions (DMRs): intergenic DMR (IG‐DMR), maternally expressed 3‐DMR (Gtl2‐DMR), and Dlk1‐DMR. Here, we report the first maternally methylated DMR, CpG island 2 (CGI‐2), is located approximately 800 bp downstream of miR‐1188. CGI‐2 is highly methylated in sperm and oocytes, de‐methylated in pre‐implantation embryos, and differentially re‐methylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The loss of genomic imprinting (LOI) expression of DLK1-Dio3 miRNAs in acute promyelocytic leukemia (APL) and type 2 diabetes mellitus (T2DM) has been associated with altered DNA methylation at Gtl2 (MEG3)-DMR region [ 52 , 53 ]. In addition, a recent study reported a new maternally methylated DMR named CGI-2-DMR, which acquires differential methylation pattern during embryonic development [ 54 ]. However, the role of CGI-2 DMR in the regulation of imprinting DLK1-Dio3 gene expression has not been addressed in the report.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of genomic imprinting (LOI) expression of DLK1-Dio3 miRNAs in acute promyelocytic leukemia (APL) and type 2 diabetes mellitus (T2DM) has been associated with altered DNA methylation at Gtl2 (MEG3)-DMR region [ 52 , 53 ]. In addition, a recent study reported a new maternally methylated DMR named CGI-2-DMR, which acquires differential methylation pattern during embryonic development [ 54 ]. However, the role of CGI-2 DMR in the regulation of imprinting DLK1-Dio3 gene expression has not been addressed in the report.…”
Section: Discussionmentioning
confidence: 99%
“…The Dlk1/Dio3 imprinted domain contains three known differentially methylated regions (DMRs) that are paternally methylated: intergenic DMR (IG-DMR), maternally expressed 3-DMR (Gtl2-DMR), and Dlk1-DMR [16]. Previous studies suggest that the IG-DMR dictates the allelic methylation status of the Gtl2 promoter DMR, which then controls gene expression across the entire cluster [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although IG-DMR and Meg3/Gtl2-DMR are paternally methylated, a maternally methylated DMR upstream of the Rtl1 gene in mice has been reported (Zeng et al, 2014). Similarly, in humans, a maternally methylated DMR was identified in the second intron of the MEG8 noncoding RNA that acquires differential methylation postfertilization (Court et al, 2014).…”
Section: Meg8-dmrmentioning
confidence: 99%